A comparison of the nutritive value of normal and opaque-2 maize for growing pigs in diets containing meat and bone meal with and without amino acid supplementation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Science at Massey University - Stables, Nigel Harry John (Massey University, 1974)
Pig meat production in New Zealand has traditionally been associated with the dairy industry, relying upon dairy by-products (principally skim-milk and whey) as major sources of protein and energy for pig feed. However, export market prospects for milk protein led to the diversification of dairy factory products, such as the ultra-filtration of whey protein and lactose extraction of whey. The prevailing economic climate also encouraged dairy farmers to change to whole milk ,anker collection and large numbers of the supplementary pig enterprises were closed down. Despite fluctuations, market prices generally showed an increase and many farmers began investigating alternative food supplies in order to take advantage of these higher prices. Garbage and other edible waste provided only limited scope for expansion, and the main alternative appeared to be the use of cereal grains. The New Zealand pig industry, in the last 5-10 years, has therefore begun to move towards a specialised form of production based upon the use of diets containing a predominance of cereals, similar to what has prevailed in many overseas countries for a longer period. The local report of Kingma and Ryan (1971) illustrates the need for efficiency in the high cost system of production based upon meal feeding. Where skimmilk is the principal ingredient in the ration, the supply of dietary protein is generally adequate due to the high nutritive value of the protein in this feedstuff. However, when the major source of nutrients comes from cereal grains, although these provide a concentrated source of energy, the poor balance of amino acids becomes limiting to the utilization of such rations. In New Zealand there is a restricted range of feeds high in protein and suitable for incorporation into pig rations. They include skimmilk powder, buttermilk powder, meat meal, meat and bone meal, liver meal and fish meal. Alternative sources of protein in soybeans, lupins, field beans and lucerne are being investigated.
Keywords: Swine; Feeding and feeds; Amino acids in animal nutrition; Corn as feed